World trade and investment law reimagined : a progressive agenda for an inclusive globalization - Santos, Alvaro, 1975-; Thomas, Chantal, 1971-; Trubek, David M., 1935- (Anthem IGLP rethinking global law and policy series., 2019)
World trade and investment law is in crisis: new and progressive ideas are needed. Rules that facilitated globalization and supported global economic growth are being challenged. A system of global governance that once seemed secure is now at risk as the US ignores the rules while developing countries struggle to escape restrictions. Some want to tear global institutions and agreements down while others try desperately to maintain the status quo. Rejecting both options, a group of trade and investment law experts from 10 countries, South and North, have joined hands to propose ideas for a new world trade and investment law that would maintain global growth while distributing costs and benefits more fairly. Paying special attention to those who have suffered from trade dislocation and to restrictions that have hampered innovative growth strategies in developing countries, they outline a progressive trade and investment law agenda in 'Globalization Reimagined' that includes new ways to link trade with protection for labour; measures to ensure that gains from trade are used to offset losses; new rules that can protect foreign investments without hamstringing developing governments or harming local communities; innovative procedures to allow developing countries the freedom to try innovative growth strategies; and methods to cope with new products.--